HUBUNGAN ANTARA PENDIDIKAN ORANG TUA DENGAN STATUS GIZI ANAK PADA KELUARGA BINAAN FK UMSU - FILIA AMANDA LUBIS; ELMAN BOY (LP2MTBM MAKARIOZ, 2020)
The problem of nutrition is no longer merely a health problem, but also the problem of education, poverty, and employmentopportunities. There are 4 sub-forms of nutritional deficiencies: wasting, stunting, underweight, and deficiencies of vitaminsand minerals. Many studies have proven that one of the basic causes of wasting and stunting is a condition of low (poor)education and family economics. This study aims to determine the relationship of the level of education of parents to thenutritional status of primary school-age children in the fostered families of the Medical Faculty of Universitas MuhammadiyahSumatera Utara. The design of this study was descriptive analytic with a cross-sectional study type. The population of thisstudy amounted to 25 mothers with 43 total childrens who were registered as members of the Fostered Family of MedicalFaculty Universitas Muhammadiyah Sumatera Utara. The sampling technique uses the total sampling method. There was norelationship between parental education and the nutritional status of children, where p values (0.200) were obtained.The most nutritional status found in this study is well nourished and there is no relationship between the level of education ofparents and the nutritional status of children in the fostered families of the Medical Faculty of Universitas MuhammadiyahSumatera Utara.